Prevalence of overweight and obesity in Chinese children and adolescents from 2015 - Yunping Zhou; Qian Zhang; Tao Wang; Yanqing Zhang; Bo Xu (Annals of Human Biology, 2017)
Background: To update the prevalence of overweight and obesity in children and adolescents from 2015. Methods: Data for this study were obtained from children and adolescents aged 7–17 years with measured weight and height from the National Surveys on Chinese Students’ Constitution and Health in 2015. Results: Measurements from 29 418 children and adolescents (14 480 boys and 14 938 girls) were analysed. Among children and adolescents aged 7–17 years, the prevalence of obesity was 13.2% (95% CI = 12.8–13.7%) in 2015. Moreover, the prevalence of obesity for children aged 7–12 years (20.3% (95% CI = 19.5–21.1%)) was significantly higher than in adolescents aged 13–17 years (9.6% (95% CI = 9.2–10.0%)) (p < 0.001). Comment: Obesity was much worse in children than adolescents in China; future studies are warranted to understand why these differences may be occurring.